Analisis Kegiatan Kelompok Kerja Guru Pendikan Agama Islam Sekolah Dasar di Kecamatan Ilir Barat Satu Palembang - Edi Rismawan; Akmal Hawi; Fajri Ismail (Bahasa Indonesia, Bahasa English, 2020)
The teacher component has a very important role especially at the elementary school level and is the main key to the success of improving the quality of education, especially in the learning process in the classroom. For this reason, the ability of teachers needs to be improved and developed through various efforts, including through education, training and professional development such as KKG. With this, researchers are interested in researching about the KKG PAI Elementary School Activities as a forum for improving the teaching profession in the IB-1 district of Palembang. This research is a qualitative descriptive study with a phenomenological, sociological, and scientific approach. The data source of this study consisted of primary and secondary sources. Data collection techniques were carried out using interviews,participatory observation, documentation, and reference tracing. Qualitative data analysis / processing techniques use 3 stages: 1) data reduction, 2) data display, and 3) data verification. The research findings are, First, the implementation of the KKG PAI SD activities in the IB-1 Kec district of Palembang, carried out in 2 (two) forms, namely routine meetings held at least once a month and incidental meetings held in accordance with the planned time period. The Second Effects of the KKG PAI Elementary School Activity in Kec IB-1 Palembang has an impact on increasing the pedagogical competence of PAI SD teachers in improving the quality of the learning process in the classroom. Third, member contributions are divided into three parts, namely contributions in the form of material, energy and ideas. The four factors supporting the implementation of KKG PAI elementary school activities in Kec IB-1 Palembang, among others: (a) educational factors, (b) age factors, (c) motivational factors. Factors inhibiting the implementation of the KKG PAI SD activities in Kec IB-1 Palembang, include: (a) lack of enthusiasm from the teachers, (b) not getting permission, (c) funding factors, (d) IT mastery factors that have not been maximally and evenly distributed.